(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Facial identification in photos or videos is a common theme in biometrics research. Many public places usually have video capture surveillance cameras and these cameras are very important for protection. Facial recognition has traditionally been recognized as a significant factor in the monitoring framework, as it does not require the cooperation with the object. The real advantages of facial authentication over other biometrics are their singularity and identification. Since the human face is a highly diverse dynamic object, computer vision makes face recognition a challenging question Accuracy and speed of identification are the main challenges in this field. This paper aims at testing various facial detection and recognition methods as an initial video monitoring phase for image-orientated face detection, and provides an entire solution with greater accuracy, greater response time. The method is recommended for subjects, posture, emotions, race and light, based on studies carried out on various face-rich databases.